Uji Kualitas Minyak Goreng Sawit yang Beredar di Entikong, Kalimantan Barat - Thamren Juniarto; Ida Diyanti Isnasia (LPPM Universitas Terbuka, 2021)
Palm cooking oil is a common food ingredient used by the community to meet their daily needs. Cooking oils distributed in the border area between Malaysia and Indonesia, especiallyaround the Entikong, West Kalimantan region are very vulnerable to counterfeiting and their qualities are unknown. This study was aimed to test the quality of cooking oils from Malaysiadistributed in the border areaof Entikong, West Kalimantan to test whether they comply with the requirements of SNI 7709: 2012 regarding Palm Cooking Oil. The cooking oil quality test includes parameters of odor, taste, color, water content, free fatty acid number, peroxidenumber, pelican oil, vitamin A and metal contamination (Pb, Cd, Hg, As and Sn). The results of this study indicated that cooking oils from Malaysia which were used as test samples met the requirements of SNI exception for peroxide number in which four of six samples didn’t meet the standard.